Analysis Factor Physical Test Muaythai Sport of Regional Training Center East Java 100 (Puslatda Jatim 100) - Soldier of Fortuna; Setiyo Hartoto; Dwi Cahyo Kartiko; Irmantara Subagio (BIRCU, 2021)
This study aims to determine how many variables of physical test items are dominant and effectively used in the sport of muaythai regional training center of east java 100. This type of research is quantitative with a development research approach. This research was conducted in 3 stages, namely stage I tabulating the test items that have been determined by the team of East Java experts, stage II processing data and reducing test items that do not meet statistical prerequisites, stage III factor analysis of all test items that meet statistical prerequisites. . The data is processed using the application (SPSS, in stage I all the results of the physical tests totaling 16 test items are entered into SPSS and processed by factor analysis, there are two variables reduced and not included in the next factor rotation, stage II thetest is carried out. Kaiser Meyer Olkin Measure of Sampling (KMO) the result is 0.640> 0.5 with the results of the barletts test 201.084 with a significance of 0.000, there is 1 variable with MSA <0.5, namely Sit and reach (S&R) of 0.493, on the communality table. Based on the results of the communality test there are two variables <0.5 variable (X5) Chin Up 0.476 and (X16) Sit and Reach 0.368 these variables do not meet the requirements of communality and must be removed from the test Stage III Bartlett Test of Sphericiry is 183.067 at a significance of 0.000 with a KMO of 0.669. The conclusionfrom the results of the factor analysis of the item physical test items for muaythai in this study, there are 5 factors that are formed from 12 variables (+ 2 sub-variables formed from variable X14) which are correlated, from the initial 16 items on physical tests (with 5 sub-variables formed from 2 variables). The dominant factor for the formation of physical test items for muaythai is items related to leg and leg muscles (square jump, wattbike, kneel-up, triple jump and hamstring), the second dominant factor is the abdominal muscles which are represented by two items (sit ups). and a russian twist).